METODE PEMBELAJARAN BLENDED LEARNING SEBAGAI SOLUSI DALAM MENGHADAPI REPOSISI PENDIDIKAN DI ERA REVOLUSI INDUSTRI 4.0 - David Rizaldy; Kristi Dese Imanuel Adi Papa Yohanes; Syu’aibul Huda (Universitas Muhammadiyah Semarang, 2018)
ducation in Indonesia has now entered an era where information technology is the main resource. This era is called the Industrial Revolution 4.0. Current learning uses three methods, namely (1) Face to face learning, (2) Fully online system and (3) Blended Learning. The Blended Learning method is to integrate face-to-face learning with an online learning system. Blended Learning learning method is a solution to the repositioning of education in the Industrial Revolution 4.0 era. The research method used is descriptive qualitative supported by literature study and secondary data collection techniques from relevant agencies. The purpose of writing this paper is to provide information related to blended learning learning methods as a teaching solution in the face of repositioning education from conventional learning towards online learning. Keywords: Blended Learning, Learning, Education, Repositioning